GEOTHERMAL-SLUDGE-BASED SODIUM SILICATE CATALYST DEACTIVATION IN METHYL ESTER PRODUCTION PROCESS - Inasanti Pandan Wangi; Indra Perdana (Indonesian Food and Nutrition Progress, 2019)
The deactivation of solid catalyst is one of the catalyst parameters that has to be known to predict how long catalyst can be used to catalyze a reaction. In this research, the catalyst was applied to catalyze the transesterification of corn oil with methanol. Sodium silicate was produced from NaOH and silica was extracted by gelation method from Dieng Geothermal Power Plant solid sludge which had 55% of silica content. Sodium silicate catalyst was activated by calcination process at 400oC, with heating rate of 20ºC/min, and holding time of 3 hours. The transesterification was run at 60oC, methanol and corn oil mole ratio of 9:1 and 5% (w/w) catalyst for 60 minutes. The sample was taken at 0, 5, 10, 20, 40 and 60 minutes after corn oil was poured into the flask. The used catalyst was separated from the reactant and product, was then washed with methanol and was heated at 120 oC in the oven for 2 hours until it dried. The catalyst was then used for catalyzing the next experiment run for the next four cycle. This research showed that the conversion of the reaction decreased with every reaction cycle. The most fitting reaction kinetics was modeled with second order kinetics. The highest conversion obtained using fresh catalyst was 91,67%.